Evaluation of fly ash geopolymer mortar incorporating calcined wastepaper sludge. Issue 6 (1st November 2016) - Yan, Shiqin; Sagoe-Crentsil, Kwesi
Abstract : This study evaluates fresh and hardened properties of fly ash geopolymer mortars incorporating calcined wastepaper sludge cured under ambient conditions. The calcined sludge geopolymer mixtures were characterized by XRD, XRF, and SEM–EDS techniques. It was observed that addition of up to 40 wt% calcined sludge in geopolymer mortars at a fixed liquid/solid mass ratio of 0.2 reduced flow of mortars from 112 to 61%, while the corresponding setting time was shortened from 113 h to just under 1 h. At the maximum calcined sludge loading of 40 wt%, the compressive strength at 7 days was 29.0 MPa, a significant increase from 3.8 MPa for reference mortar samples with no addition of sludge. Correspondingly, a nearly fourfold reduction in 56-day drying shrinkage measured at 3600 microstrains was observed, compared to reference mortars. The plausible reaction mechanisms, in particular, apparent concurrent formation of C-A-S-H/N-(C)-A-S-H phases alongside geopolymer gel networks are discussed in detail.